â€œTraffic Congestion and Speed Delays at Benz Circle, Vijayawada Due to Construction Activitiesâ€, A Case Study - Akhila, B; Sai Krishna, K; Sri Nikhil, M; Narra, Malathi (International Journal of Engineering and Technology, 2018)
In urban areas, traffic congestion is a major problem. Heavy traffic flow on National Highways with high speed, when mixed up with local traffic at crossings, traffic congestion is likely to occur. This causes many negative effects like pollution, delay, accidents and improper traffic management at crossings. At Benz circle one of the rotary intersections in Vijayawada, the above problem frequently occurs. To reduce the ill effects, some solution is needed to be provided. So, as a solution- Construction of flyover at this intersection is proposed and accepted as the best alternative or solution for the problem. For this classified volume count survey and analysis is carried out and the capacity of the existing lane is checked. But in the mean-time of construction there might be increase in the traffic congestion and speed delays due to the diversion of routes.Â